Risk Factors of Periprocedural Bradycardia during Primary Percutaneous Coronary Intervention in Patients with Acute ST-Elevation Myocardial Infarction - Yong Li; Shuzheng Lyu (Cardiology Research and Practice)
Background. Evidence available suggests that periprocedural bradycardia negates the benefit of primary percutaneous coronary intervention (PPCI) and worsens the prognosis of patients with acute ST-elevation myocardial infarction (STEMI). Objective. To investigate the risk factors of periprocedural bradycardia during PPCI in patients with acute STEMI. Methods. We enrolled 2,536 acute STEMI patients who had PPCI from November 2007 to June 2018 in Beijing Anzhen Hospital, Capital Medical University. We divided all patients into two groups according to periprocedural bradycardia (preoperative heart rate ≥50 times/min, intraoperative heart rate <50 times/min persistent or transient) during PPCI: periprocedural bradycardia group (434 cases) and control group (2102 cases). We compared demographic, clinical, and angiographic characteristics of the two groups. We analyzed the risk factors of periprocedural bradycardia. Results. The incident rate was 17.1% (434/2536). Logistic regression analysis showed that the differences between the two groups in no-reflow, the culprit vessel was LAD, using thrombus aspiration devices during operation, gender, completely block of culprit vessel, and intraoperative hypotension were statistically significant (P<0.05). The area under the receiver operating characteristic curve was 0.8390. Conclusions. No-reflow, the culprit vessel was not LAD, using thrombus aspiration devices during operation, gender, completely block of culprit vessel, and intraoperative hypotension may be independent risk factors for predicting periprocedural bradycardia during PPCI in patients with acute STEMI. We registered this study with WHO International Clinical Trials Registry Platform (ICTRP) (registration number: ChiCTR1900023214; registered date: 16 May 2019).